Utilization of multimedia resources in nuclear sciences communication within the Brazilian school environment - Vitor Fernandes Almeida; Amir Zacarias Mesquita; Alexandre Soares Leal; Fernando Soares Santos; Rodrigo Vieira Pereira; Valéria Emiliana Alcântara e Alves; Adriano Almeida Massaud Felippe; Ana Rosa Baliza Maia; Leonardo Yago Zwetsch Varella; Walewska Gouveia Silva (Brazilian Journal of Radiation Sciences)
Brazil holds a promising future in nuclear technology, as evidenced by significant investments such as the construction of the Brazilian Multipurpose Reactor and the completion of the country's third nuclear power plant, Angra 3. However, scientific communication regarding the benefits and applications of nuclear technology still requires strengthening to enhance public acceptance. In this context, multimedia resources have proven to be an effective tool for promoting meaningful learning about nuclear technology among high school students. Following the lessons, 97.76% of students perceived a gain in knowledge about nuclear technologies, and 86.64% reported a more positive attitude towards nuclear science. Additionally, 84% of students expressed increased favorability towards radiation applications, and support for nuclear energy as a clean energy source rose from 43.84% to 84.88%. These results indicate that multimedia not only facilitated understanding of complex concepts but also contributed to a more favorable perception of nuclear technology among students. This outcome is crucial for fostering an informed culture regarding the importance of nuclear technology, ensuring that future professionals and decision-makers are well-acquainted with its benefits and applications.